The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/1809-6891v23e-72352e
|View full text |Cite
|
Sign up to set email alerts
|

Mixed silages of sugarcane and forage peanut treated with Lactobacillus buchneri

Abstract: There is evidence for the beneficial effects of forage peanut on the nutritive value and fermentation profile of silages; however, its effects on sugarcane silage have not been determined. The objective of the study was to evaluate the chemical composition, fermentation profile, microbial composition, and dry matter recovery (DMR) of sugarcane silage containing various amounts of forage peanut (Arachis pintoi cv. Belmonte) (0%, 25%, 50%, and 75% on a fresh matter basis), treated or untreated with Lactobacillus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…In contrast, L. buchneri, a heterofermentative LAB, enhances silage's aerobic stability by converting LA into acetic acid (AA), thereby inhibiting filamentous fungi growth (Yin et al, 2023). da Costa et al (2022) reported that L. buchneri inoculation increased AA concentration and reduced yeast and ethanol content in sugarcane and peanut silages. Current research on whole-plant corn-soybean predominantly focuses on the intercropping model and the corn-soybean ratio during silage processing (Kizilsimsek et al, 2017;Ni et al, 2018;Zeng et al, 2020;Meng et al, 2022), and the above two mixed silage methods are also limited by nutrient loss and incomplete fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, L. buchneri, a heterofermentative LAB, enhances silage's aerobic stability by converting LA into acetic acid (AA), thereby inhibiting filamentous fungi growth (Yin et al, 2023). da Costa et al (2022) reported that L. buchneri inoculation increased AA concentration and reduced yeast and ethanol content in sugarcane and peanut silages. Current research on whole-plant corn-soybean predominantly focuses on the intercropping model and the corn-soybean ratio during silage processing (Kizilsimsek et al, 2017;Ni et al, 2018;Zeng et al, 2020;Meng et al, 2022), and the above two mixed silage methods are also limited by nutrient loss and incomplete fermentation.…”
Section: Introductionmentioning
confidence: 99%